CONTINUITY OF GENERATIONS AS A FACTOR IN THE FORMATION OF THE INTERNAL POLICY OF THE PEOPLE’S REPUBLIC OF CHINA - А.Б., Кaрaбaсовa; Н.А., Алдaбек (Journal of Oriental Studies, 2019)
Nowadays, the People’s Republic of China is one of the most dynamically developing countries and the second largest economy in the world. For this reason, the success of the “policy of reform and openness” that began in 1978 of the last centuries under the auspices of Deng Xiaoping and continued by subsequent generations of Chinese leaders in China still arouses the interest of the world community. The article attempts to analyze the role of the continuity of generations in China’s politics as one of the most important factors in the construction of socialism with “Chinese characteristics”, examines the re- lationship between the main concepts of China’s development. Some of the results of the 19th Congress of the CPC are also analyzed. Key words: Chinese leaders, Deng Xiaoping, Xi Jinping, “Socialism with Chinese characteristics”, “Chinese dream”, Chinese Communist Party.